INTEGRATION OF GREENROOF AND SOLAR PHOTOVOLTAIC SYSTEM - Mohan, Aparna M; U A, Ajna; Devassy, Anjaly; Devassy, Anjaly; N, Remyasree K; MG, Gireeshan (International Journal of Psychosocial Rehabilitation, 2020)
Modern agriculture uses different types of greenhouse system. Green roof and solar photovoltaic systems are two technologies that could contribute to sustainable building development and reduction of greenhouse gas emission. The production of healthy crops and improved quantity can be succeeding through these two technologies. The growth of plant is controlled by the environmental condition like temperature, humidity and moisture through the system we can able to protect the crops from insects, weather conditions and diseases and also the green house will be reduce all the short coming for unhealthy seasonable crop and power consumption possible by solar power.